Prevalence of intestinal helminth infections in Jiangsu Province, eastern China; a cross-sectional survey conducted in 2015 - Dai, Yang (BMC Infect Dis, 2019)
BACKGROUND: Intestinal helminth infections are a serious public health problem in developing countries. Jiangsu, an eastern coastal province of China, has an environment conducive to the transmission of intestinal parasites, and suffered human infection rates of 71.75% in 1990. Due to comprehensive anti-transmission measures undertaken throughout the province in the 1990s, the prevalence had decreased to 9.28% in 2002. In order to assess the current epidemic situation for intestinal parasitic infections in Jiangsu province, a province-wide cross-sectional survey was carried out in 2015. METHODS: Surveys were conducted in two main settings; rural (for soil-transmitted parasites) and urban (for Clonorchis sinensis), selected through stratified random sampling. Human infection rates were evaluated through the detection of helminth eggs or cysts (oocysts or trophozoites) of intestinal protozoa in fecal samples by microscopy. Secondary intermediate and reservoir hosts were surveyed for C. sinensis infection. Questionnaires were completed by each participant to evaluate knowledge, attitude and practice of soil-transmitted parasite and C. sinensis avoidance. RESULTS: 115 out of 30153 participants (0.38%) had intestinal helminths or protozoa. There were eight species of helminth detected and the most common parasite was the hookworm Ancylostoma duodenale. In rural settings, there were significant differences in infection rates between participants of differing economic status. In urban settings, only four cases of C. sinensis infection were detected. However, secondary intermediate and reservoir hosts were found to harbor parasites. The questionnaire survey revealed that 38.42% participants were not aware of how humans become infected by hookworms. Knowledge and awareness of C. sinensis was similarly low, with 53.22% participants combining the use of chopping boards for raw and cooked food items when preparing meals. CONCLUSIONS: The prevalence of intestinal parasitic infections in Jiangsu Province in eastern China has decreased from 71.57% in 1990 to 0.38% in 2015. Control measures should now focus on parasitic infections in the elderly and in children, health promotion and the development of alternative detection methods. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12879-019-4264-0) contains supplementary material, which is available to authorized users.